Crystal structure of bis(tetramethylthiourea-κS)bis(thiocyanato-κN)nickel(II) - Jochim, Aleksej (Acta Crystallogr E Crystallogr Commun, 2020)
In the course of our investigations regarding transition-metal thiocyanates with thiourea derivatives, the title compound, [Ni(NCS)(2)(C(5)H(12)N(2)S)(2)], was obtained. The asymmetric unit consists of one thiocyanate anion and one tetramethylthiourea molecule on general positions, as well as one Ni(II) cation that is located on a twofold rotational axis. In this compound, discrete complexes are formed in which the Ni(II) cations are surrounded by two trans-N-bonding thiocyanate anions as well as two trans-S-bonding tetramethylthiourea molecules within a distorted square-planar coordination geometry. The discrete complexes are linked by pairs of weak C—H⋯S hydrogen bonds between the thiocyanate S and one of the tetramethylthiourea methyl hydrogen atoms into chains along the crystallographic a- and c-axis directions, which are combined into layers parallel to the ac plane. X-ray powder diffraction proves that a pure crystalline phase was obtained and measurements using thermogravimetry and differential thermoanalysis reveal that the compound decomposes at about 408 K, where all tetramethylthiourea molecules are lost.